Crenças Sociais acerca das diferenças entre homens e mulheres e suas relações com a Percepção da Violência do homem contra a mulher - Almeida, Juliana Barbosa Lins de (2007)
Violence against women is a complex social phenomenon due to the multiplicity of its forms of expression and its realization comes from several perceptual dimensions. Because it is inherently a phenomenon engendered in the heart of patriarchal culture, many of our beliefs are already spread by force of habit. The social permissiveness of violence of man against the woman provides a kind of "free pass" for men committing various expressions of violence, without it being perceived and treated as such. You can see this in our everyday relations by double talk and double standards when assessing violence. Thus, the present study had as main objective to analyze the phenomenon of violence against women as a social and gender analysis of the proposed relationship between essentialist beliefs and social constructivists on the differences between men and women and the perception of violence of man against the woman. The program was held in the city of João Pessoa, Paraíba in a sample of 449 students between high school and college. The instruments were used, as well as socio demographic questionnaire, a range of social beliefs about the differences between men and women and a questionnaire of social perceptions of violence of man against the woman, who, from stories that reported cases of violence, assessed the perception from the dimensions of the community, categorization, and the justification of punishment. The results were analyzed using SPSS 13.0. After descriptive analysis of the evaluative dimensions of the perception of violence, it was noted that, in general, the types of violence of men against women salient perception are physical violence and sexual violence. The data also showed that both the relative position of the subjects in the social context of violence and their commitment to an essentialist position naturalizing or a social constructivist position affect the perception and the social construction of the meanings of violence of men against women.